Industry-compatible silicon spin-qubit unit cells exceeding 99% fidelity - Paul Steinacker; Nard Dumoulin Stuyck; Wee Han Lim; Tuomo Tanttu; MengKe Feng; Santiago Serrano; Andreas Nickl; Marco Candido; Jesus D. Cifuentes; Ensar Vahapoglu; Samuel K. Bartee; Fay E. Hudson; et al. (Nature, 2025)
Abstract Among the many types of qubit presently being investigated for a future quantum computer, silicon spin qubits with millions of qubits on a single chip are uniquely positioned to enable quantum computing. However, it has not been clear whether the outstanding high-fidelity operations and long coherence times shown by silicon spin qubits fabricated in academic settings1–8 can be reliably reproduced when the qubits are manufactured in a semiconductor foundry9–11. Here we show precise qubit operation of silicon two-qubit devices made with standard semiconductor tooling in a 300-mm foundry environment. Of the key metrics, single- and two-qubit control fidelities exceed 99% for all four devices, and the state preparation and measurement fidelities reach up to 99.9%, as evidenced by gate set tomography. We report spin lifetime and coherence up to T 1 = 9.5 s, $${T}_{2}^{* }=40.6\,{\rm{μ }}{\rm{s}}$$ T 2 * = 40.6 μ s and $${T}_{2}^{{\rm{Hahn}}}=1.9\,{\rm{ms}}$$ T 2 Hahn = 1.9 ms . We determine that residual nuclear spin-carrying isotopes contribute substantially to operational errors, identifying further isotopic purification as a clear pathway to even higher performance.